The analysis of morphological stability of a recrystallization front - Movchan, O.V.; Chornoivanenko, K.O. (Успехи физики металлов, 2018)
A generalization of theoretical information about the patterns of trans-formation of a conversion front during phase reactions is carried out. The theory of concentration supercooling based on diffusional redistribution of alloy components in a melt near crystallization boundary is considered. Transformation mechanisms of flat front of crystallization with structure change into cellular and dendritic are studied. Regulations of the interfacial boundary instability during the phase transition are considered. The effect of alloying elements on the morphology of the transformation front is analysed. The conditions of the morphological stability of the recrystallization front in the high-alloyed iron alloys during chemical-thermal treatment are considered. As established, the transformation of the conversion front is carried out under the action of concentration gradients. This is caused by the redistribution of the base alloying elements ahead of the recrystallization front.